2020
DOI: 10.3390/bioengineering7030102
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning Decellularized ECM as a Bioactive Surface to Guide Cell Alignment, Proliferation, and Migration

Abstract: Bioactive surfaces and materials have displayed great potential in a variety of tissue engineering applications but often struggle to completely emulate complex bodily systems. The extracellular matrix (ECM) is a crucial, bioactive component in all tissues and has recently been identified as a potential solution to be utilized in combination with biomaterials. In tissue engineering, the ECM can be utilized in a variety of applications by employing the biochemical and biomechanical cues that are crucial to rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…The investigation of the in vitro NIH 3T3 cell culture described in the paper confirmed the practical applicability of the proposed IPC-CE construct for biomedical applications, as well as its structural robustness and the topographical effect of the micro-ridge patterns. Many previous studies have shown that the NIH 3T3 cells tend to be elongated and oriented along anisotropic topographies, as a result of contact guidance by nanoscale patterns or geometrical confinement by microscale patterns (>10 μm) [ 6 , 33 , 34 , 35 ]. Our results showed that the micro-ridge patterns on the IPC-CE construct favorably promoted both the elongation and orientation of cells along the micro-ridges by geometrical confinement, which stably maintained their structure during the cell culture period, whereas the conventional constructs lost their topographical effect following rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the in vitro NIH 3T3 cell culture described in the paper confirmed the practical applicability of the proposed IPC-CE construct for biomedical applications, as well as its structural robustness and the topographical effect of the micro-ridge patterns. Many previous studies have shown that the NIH 3T3 cells tend to be elongated and oriented along anisotropic topographies, as a result of contact guidance by nanoscale patterns or geometrical confinement by microscale patterns (>10 μm) [ 6 , 33 , 34 , 35 ]. Our results showed that the micro-ridge patterns on the IPC-CE construct favorably promoted both the elongation and orientation of cells along the micro-ridges by geometrical confinement, which stably maintained their structure during the cell culture period, whereas the conventional constructs lost their topographical effect following rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…To control cell shape and area by micropatterning, PDMS stamps with square/rectangular or line patterns were prepared by standard photolithography using photoresist SU-8 2010 (Microchem Corp, Newton, MA, USA), which is detailed elsewhere [ 14 , 91 ]. The patterned side of the PDMS stamp was incubated with 50 µg/mL laminin solution for 1 h before bringing it into conformal contact with the cell culture substrate for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Another feature of these platforms is their composition; in healthy tissue, ECM plays a vital role in supporting cell growth and behavior by providing structural, mechanical, and bioactive cues . In recent years, single and multiple ECM proteins have been incorporated into polymer scaffolds to improve their biocompatibility and function. However, a single protein cannot mimic all functions attributed to whole ECM. , Whole-organ decellularized ECM incorporated into artificial scaffolds has shown advantages such as affecting hydrophilicity, cell adhesion, proliferation, and behavior. , This has also been seen with hepatocytes, with studies showing that rat and human liver dECM can impact cell survival and proliferation. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…To date, the focus on scaffold topography and dECM combinations has mainly been investigated on the macroscale. , However, limited attention has been devoted to the synergistic effects of topographical and biochemical cues on hepatocytes for liver tissue engineering. We have therefore developed a new protocol to incorporate the perfusion of whole-organ decellularized rat liver ECM into electrospun fibers with surface depressions to explore the combined effect on human hepatic carcinoma cells (HepG2).…”
Section: Introductionmentioning
confidence: 99%